-7z-8=-8z

Simple and best practice solution for -7z-8=-8z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7z-8=-8z equation:


Simplifying
-7z + -8 = -8z

Reorder the terms:
-8 + -7z = -8z

Solving
-8 + -7z = -8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8z' to each side of the equation.
-8 + -7z + 8z = -8z + 8z

Combine like terms: -7z + 8z = 1z
-8 + 1z = -8z + 8z

Combine like terms: -8z + 8z = 0
-8 + 1z = 0

Add '8' to each side of the equation.
-8 + 8 + 1z = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 1z = 0 + 8
1z = 0 + 8

Combine like terms: 0 + 8 = 8
1z = 8

Divide each side by '1'.
z = 8

Simplifying
z = 8

See similar equations:

| -(8x-4)=-4x-3(x-3) | | 15.16+13.5k=-4.86+12.1k | | 15000/3= | | 7+2g=3g | | 15000%3= | | 11x-2y= | | -16x-14= | | 7m-8=7-8m | | 18-6c=-18-4c | | 4x^2-3x-5=-4 | | 5x+3(2x-1)=4(3x+5)-8 | | -18+6z-6=10+8z | | 101+10x+9=180 | | -3(1+6r)=11115-r | | s=70-28 | | -7r=-8r+13 | | 4-6(x-2)=26-9x | | 2x-6=4x-8 | | 8-7g=-4g-7 | | (5a-2)(5a+2)=0 | | 3x=2(x+123456) | | -8s=5-9s | | x+139+x+59=180 | | y+7=-5y+8y-7 | | 800x-550=66 | | x^2+96=x^2 | | -5r-3=3-4r | | -8+3n=n+6 | | -3(m-25000)=2(100-m) | | -6+3t=t+10 | | 7.93x+23.79=47.58 | | -3m=-10-5m |

Equations solver categories